Analysis of ball speed and accuracy of groundstrokes on a clay court in young - Sangkaew, T.; Phongsri, K.; Khamros, W.; Mohamad, N. I.; Sriramatr, S. (Journal of Physical Education and Sport, 2024)
Accuracy and speed are critical factors that influence tennis performance. Various studies have examined speed, but less attention has been given to understanding the probabilistic structure of errors (i.e., accuracy). Tennis, a racquet sport requiring high physical fitness during competition, emphasizes the importance of both ball accuracy and speed for success. This is especially true for young male competitive tennis players. This study aimed to analyze the ball accuracy and ball speed of running groundstrokes on a clay court. Sixteen males at national-level junior tennis were assessed (age: 15.50 ± 0.63 years; height: 178.44 ± 8.08 cm; body weight: 67.25 ± 7.72 kg; body mass index: 21.12 ± 1.93 kg/m²). All participants measured running groundstroke performances by hitting a ball to a target square and hitting it as fast as possible by using a ball machine that fed 10 balls at a velocity of 60 km/h, with a 2-minute break between trials. The running groundstroke variables measured included Running Forehand Down the Line (RFDL), Running Forehand Cross-Court (RFCC), Running Backhand Down the Line (RBDL), and Running Backhand Cross-Court (RBCC). The results found that the forehand technique was a more accurate skill than the backhand, with higher averages than other skills (RFCC; 1.81±0.544 RFDL; 0.37±0.500, RBDL; 0.25±0.447, RBCC; 0.62±0.719) p = 0.011. The forehand technique also showed a higher average speed, particularly in RFCC (p = 0.001). The Pearson correlation of forehand techniques in RFCC and RFDL was moderately related, r = .697, with statistical significance at p = 0.05. These results suggest that the differences in groundstroke running each technique are different. Thus, coaches should adopt specific training programs focusing on ball accuracy and ball speed to enhance the performance of youth tennis players on clay courts.